The Pharmaceutical Firms of Pakistan: An Overview of Multidimensional Performance - Ali, Dr. Majid; Sarwar, Dr. Gulam; Saboor, Dr. Abdul (Journal of Peace, Development and Communication, 2021)
The pharmaceutical industry of Pakistan is now meeting around 80% of total domestic demand with an annual11% growth rate. But the question arises as to whether the firms produce efficiently? The paper measures cost efficiency of the pharmaceutical industry of Punjab using Data Envelopment Analysis (DEA) for the period of 2014-15. The factors affecting the cost efficiency is also determined by using Tobit method. In first stage, value added is used as single output and number of employs, raw material, and cost of salary are as inputs. The result suggested that the cost efficiency of the pharmaceutical firms is 27.7% which is determined by 46% technical efficiency (TE) and 60.8% allocative efficiency (AE). It means wastage of resources is cost increasing factors in these firms. In the second stage, among the variables i.e. firm’s market share, firm’s Herfindahl-Hirschman Index (HHI) of market concentration, values of assets, energy, Herfindahl-Hirschman Index has strong positive effect on cost efficiency.